Assessing the psychometric properties of persian version of Zarit Burden interview among family caregivers of patients with multiple sclerosis - Hajar Haghshenas; Zeinab Jokar; Ladan Zarshenas; Mahnaz Rakhshan; Maryam Poursadeghfard (BMC, 2023)
Abstract Background Caring for patients with multiple sclerosis (MS) imposes a great burden on caregivers and affects their lives in various aspects. This study aimed to evaluate the psychometric properties of Persian version of 22-item Zarit Burden Interview (ZBI-22) among family caregivers of patients with MS. Methods This methodological study was conducted in Fars province, southern of Iran. For this purpose, 120 family caregivers were recruited to participate in the study from January to March 2022. Zarit Burden Interview (ZBI) was translated into Persian through forward-backward method. Face and content validity were assessed. Construct validity was assessed using exploratory factor analyses (EFA), and its reliability was assessed by measuring internal consistency and testretest stability. Results According to face validity, the impact scores of all items were more than 1.5. Content validity ratio and content validity index values of all 22 items were 0.64-1 and 0.82-1, respectively. The scalelevel CVI/Ave was 0.97. Based on the results of factor analysis, five factors with eigenvalues more than 1 were extracted, which altogether explained 62.62% of the total variance of ZBI score. Among 22 items, one item was deleted during EFA validity assessment. Factor loading values ranged from 0.40 to 0.88. The reliability of the scale was confirmed (total Cronbach's alpha of the ZBI = 0.88). Moreover, testretest stability assessment revealed no significant difference between test and retest scores (P > 0.05). The intraclass correlation (ICC) for the ZBI and ICCs among its factors were 0.88 and 0.6-0.86, respectively. Conclusion The Persian version of five-factor structure ZBI can be a valid and reliable scale, and it can be used to assess caregiver burden among family caregivers of patients with MS in Iran.